2016
DOI: 10.1111/and.12706
|View full text |Cite
|
Sign up to set email alerts
|

Porcine sperm vitrification I: cryoloops method

Abstract: The aims of this study were to evaluate porcine sperm vitrification in cryoloops, with and without two different cryoprotectants and assess two warming procedures. Extended (n = 3; r = 4) and raw (n = 5; r = 2) semen was diluted in media without and with cryoprotectants (4% dimethylformamide and 4% glycerol) to a final concentration of 20 × 10 spermatozoa ml and vitrified using the cryoloops method. Two warming procedures were evaluated: rapid method (30 s at 37°C) and an ultra-rapid method (7 s at 75°C, follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 45 publications
1
10
0
4
Order By: Relevance
“…Esto permite, utilizar al DTT o al ME como controles positivos de la tinción con AT. Esta tinción se ha utilizado en varias especies para detectar defectos en la condensación de la cromatina (humano: Barrera et al, 1993;Erenpreiss et al, 2001;Erenpreisa et al, 2003;Tsarev et al, 2009;toro: Beletti y Mello, 1996;Beletti et al, 2005;conejo: Beletti y Mello, 2004;padrillo equino: Naves et al, 2004;Sardoy et al, 2008;Carretero et al, 2012a) y actualmente se ha empleado para evaluar la cromatina en caninos, felinos y porcinos (Monachesi y Carretero, 2014;Allera et al, 2016;Arraztoa et al, 2016).…”
Section: Revisión Del Temaunclassified
See 2 more Smart Citations
“…Esto permite, utilizar al DTT o al ME como controles positivos de la tinción con AT. Esta tinción se ha utilizado en varias especies para detectar defectos en la condensación de la cromatina (humano: Barrera et al, 1993;Erenpreiss et al, 2001;Erenpreisa et al, 2003;Tsarev et al, 2009;toro: Beletti y Mello, 1996;Beletti et al, 2005;conejo: Beletti y Mello, 2004;padrillo equino: Naves et al, 2004;Sardoy et al, 2008;Carretero et al, 2012a) y actualmente se ha empleado para evaluar la cromatina en caninos, felinos y porcinos (Monachesi y Carretero, 2014;Allera et al, 2016;Arraztoa et al, 2016).…”
Section: Revisión Del Temaunclassified
“…La concentración del colorante utilizado en la tinción varia entre las especies, sin embargo, en la llama, alpaca, guanaco, equino, felino, canino y porcino se observaron los mismos patrones de coloración a pesar de la diferente concentración de AT: coloración celeste (negativos, sin alteración en la condensación normal de la cromatina), violeta claro (intermedios, algún grado de descondensación) y violeta-azul oscuro (positivos, alto grado de descondensación) (Sardoy et al, 2008;Carretero et al, 2009;2010a, 2010b2012a;Monachesi y Carretero, 2014;Allera et al, 2016;Arraztoa et al, 2016). Los patrones AT positivos y AT intermedios son considerados espermatozoides con alteración en la condensación de la cromatina.…”
Section: Revisión Del Temaunclassified
See 1 more Smart Citation
“…Many of these techniques require complex instruments that often are not available in animal reproduction centres. TB is simple and inexpensive and has been used to evaluate the degree of chromatin condensation in various species (humans: Barrera, Mazolli, Pelling, & Stockert, ; Erenpreiss, Bars, Lipatnikova, Erenpreisa, & Zalkalns, ; Erenpreiss et al, ; Erenpreisa et al, ; Tsarev et al, ; bulls: Beletti, Fontoura Costa, & Mendes Guardieiro, ; Beletti & Mello, ; Vieytes, Cisale, & Ferrari, ; Dogan et al, ; rabbits: Beletti & Mello, ; stallions: Carretero, Arraztoa, et al, ; Naves et al, ; Sardoy, Carretero, & Neild, ; South American Camelids: Carretero, Arraztoa, et al, ; Carretero, Giuliano, et al, ; Carretero, Giuliano, Casaretto, Gambarotta, & Neild, , pigs: Arraztoa et al, ; González et al, , and cats: Allera, Comercio, Gonzales Vera, Miragaya, & Carretero, ). To increase the sensitivity of the technique, many of the above‐mentioned studies used acid hydrolysis prior to staining with TB (Beletti et al, ; Beletti & Mello, ; Erenpreisa et al, ; Erenpreiss et al, , ; Tsarev et al, ); however, this increases the length and the cost of the technique.…”
Section: Introductionmentioning
confidence: 99%
“…To increase the sensitivity of the technique, many of the above‐mentioned studies used acid hydrolysis prior to staining with TB (Beletti et al, ; Beletti & Mello, ; Erenpreisa et al, ; Erenpreiss et al, , ; Tsarev et al, ); however, this increases the length and the cost of the technique. In dogs, there is only one report of using hydrolysis prior to staining (Flores et al, ), and no study has reported TB staining canine sperm without prior hydrolysis as has been described in other species (Allera et al, ; Arraztoa et al, ; Carretero, Arraztoa, et al, ,; Carretero, Giuliano, et al, ; Carretero et al, ; Sardoy et al, ). For this reason, the objectives of this study were as follows: (a) simplify the TB technique for evaluating chromatin in canine raw semen, (b) verify the staining patterns for this species using this simplified technique and (c) establish a protocol for using dithiothreitol (DTT) as a positive control for TB staining in dogs.…”
Section: Introductionmentioning
confidence: 99%